Preferences for pandemic recovery policies: Perspectives of Myanmar agri‐food system participants - Maredia, Mywish K.; Goeb, Joseph; Ortega, David L.; Synt, Nang Lun Kham; Zu, A Myint (Wiley, 2022)
This study assesses preferences for COVID‐19 pandemic recovery policies from four key groups representing the upstream (input retailers), farm (farmers), and downstream (millers and traders) levels of Myanmar's agri‐food‐system using the best–worst scaling (BWS) method. Our results show that nonrestrictive policies such as maintaining open international borders and allowing businesses to stay open are preferred to cash transfers and free COVID‐19 vaccination. However, there is considerable heterogeneity across groups, and group characteristics matter more than individual characteristics in shaping policy preferences. This paper highlights the need for careful consideration of diverse stakeholder perspectives in designing recovery policies.